Quality of educational service in public universities in Ecuador: a sustainable and equitable education approach - Zapatier Castro, Sonnia Valeria; Noriega Verdugo, Delia Dolores; Farías Lema, Ruth María; Peña Holguín, Ruth Rubí; Valenzuela Cobos, Juan Diego (Frontiers in Education, 2025)
IntroductionPublic universities in Ecuador face persistent structural and contextual challenges that affect the delivery of quality education. Despite institutional efforts, significant gaps remain between student expectations and perceived service quality.MethodsThis study used the HEdPERF model to assess students’ perceptions of educational service quality at a public university in Ecuador. A structured digital questionnaire was administered to a stratified random sample of 1,500 students across four faculties. Confirmatory Factor Analysis (CFA) and Principal Component Analysis (PCA) were employed to validate the model and identify key dimensions influencing satisfaction.ResultsThe CFA results showed excellent fit indices (CFI = 0.997, TLI = 0.997, RMSEA = 0.020), confirming the validity of the HEdPERF structure in this context. Reliability was also high, with Cronbach’s Alpha and Composite Reliability (CR) exceeding 0.70. PCA identified that non-academic factors such as infrastructure, access to services, and university reputation had a stronger influence on students’ perceptions than academic factors.DiscussionThe findings highlight the importance of integrating both academic and non academic dimensions into institutional quality strategies. Continuous assessment, curriculum innovation, and equitable access to services are essential to improving student satisfaction and promoting sustainable and inclusive education in Ecuador’s public universities.